Natural radionuclides in soil profiles and sediment cores from Jundiaí reservoir, state of Sao Paulo. - Pedro do Nascimento Gonçalves; Sandra Regina Damatto; Lucio Leonardo; Joseilton Marques Souza (Brazilian Journal of Radiation Sciences)
The activity concentration of natural radionuclides in soils and sediments is dependent on many factors, such as the rock parental material, pedogenic and weathering processes, physical and chemical properties of the environment, anthropogenic sources, among other aspects. There are few studies about the levels of natural radionuclides in reservoirs in both, international and national, literature. The objective of this paper was to evaluate the activity concentrations of 238U and 232Th by Instrumental Neutron Activation Analysis and 226Ra, 210Pb, 228Ra, 228Th and 40K by gamma spectrometry in two soil profiles and three sediment cores collected in the catchment area of Jundiai reservoir, located in the state of São Paulo, Brazil. Principal component analysis was applied to verify the correlation of the activity concentrations of the natural radionuclides with physical and chemical properties of soil and sediment samples.  The mean activity concentrations of the radionuclides in the soil profiles 1 and 2 were, respectively: 238U – 37(1) and 32(1) Bq.kg-1; 232Th – 91(1) and 60(1) Bq.kg-1; 226Ra – 66(1) and 51(1) Bq.kg-1; 210Pb – 35(1) and 37(1) Bq.kg-1; 228Ra – 34(1) and 27(1) Bq.kg-1; 228Th – 78(1) and 58(1) Bq.kg-1; 40K – 96(2) and 171(7) Bq.kg-1. For the three sediment cores analyzed, the average activities  concentrations of the radionuclides were, respectively: 238U – 64(0.5), 47(0.1) and 44(0.2) Bq.kg-1; 232Th – 122(2), 100(1) and 64(1) Bq.kg-1; 226Ra – 74(2), 71(1) and 45(1) Bq.kg-1; 210Pb – 70(3), 56(2) and 55(2) Bq.kg-1; 228Ra – 53(1), 41(1) and 33(1) Bq.kg-1; 228Th – 100(2), 92(1) and 63(2); 40K – 316(5), 237(1) and 136(2) Bq.kg-1.